A comparison of a multi-body model and 3D kinematics and EMG of duble-leg circle on pommel horse - Qian, J.-G.; Su, Y.; Song, Y.-W.; Qiang, Y.; Zhang, S. (Journal of Human Kinetics, 2012)
The purpose of this study was to establish a multi-segment dynamic model in the LifeMOD to examine kinematics of the center of mass and foot, and muscle forces of selected upper extremity muslces during a double-leg circle (DLC) movement on pommel horse in gymnastics and compared with three-dimensional kinematics of the movement and surface electromyographic (sEMG) activity of the muscles. The DLC movement of one elite male gymnast was collected. The three-dimensional (3D) data was imported in the Lifemod to create a full-body human model. A 16-Channel surface electromyography system was used to collect sEMG signals of middle deltoid, biceps brachii, triceps brachii, latissimusdorsi, and pectoralis major. The 3D center of mass and foot displacement showed a good match with the computer simulated results. The muscle force estimations from the model during the four DLC phases were also generally supported by the integrated sEMG results, suggesting that the model was valid. A potential application of this model is to help identify shortcomings of athletes and help establish appropriate training plans errors in the DLC technique during training.